Transforming Governance in Armenia: From Soviet Legacy to Strategic Reform - Margaryan, Marina (Journal of Political Science: Bulletin of Yerevan University, 2025)
This article analyzes the evolution of institutional reforms in the public administration system of the Republic of Armenia since its independence in 1991. In this context, it is taken into account that only the state is able to ensure the co-evolution of management technologies to achieve global goals and strategic objectives of the development of Armenian society. Technological dominants of political transformations, social and economic development require appropriate management adaptation, which is the focus of this study is the correct development and application of the functionality of decision support systems. Therefore, this study considers four stages of reforms: 1) Initial institutional creation from 1991 to 1999; 2) Formalization and adoption of Western governance models from 2000 to 2008; 3) European integration and administrative modernization from 2009 to 2017; 4) Political transformation accompanied by renewed administrative reforms since 2018. These reforms reflect a complex interplay of historical legacies, external influences, and internal aspirations for public administration modernization. Issues such as institutional inertia, limited localization of imported models, and political resistance are assessed in detail. In addition, the article compares these historical reforms with Armenia’s long-term goals outlined in the Public Administration Reform Strategy of the Republic of Armenia until 2030, emphasizing the transition from imitation reforms to sustainable institutional transformation.